Seismic response of 4-legged fixed offshore structure in Malaysia due to surrounding earthquake - Hong, Jia Hi (2015)
Fixed offshore structure in Malaysia region are placing more emphasis on wind and wave effects analysis rather than seismic effect. However, Malaysia actually experienced tremors due to the earthquakes occurred in the neighbouring countries. Thus, the main objective of this study is tantamount to investigate the seismic vulnerability of existing fixed offshore structures in Malaysia region and determine the necessity of seismic design consideration for offshore structure in Malaysia. With this, a finite element seismic response simulation of a typical 4-legged fixed offshore structure using SAP2000 has been presented. Moreover, free vibration, time history and response spectrum analysis have been carried out and compared throughout this study. However, there is an assumption have been made when doing the 3D model of the structure. The fixed offshore platform structure is fixed to the ground instead of pilled and the soil interaction was neglected. Generally, fixed offshore structures in Malaysia region are capable of resisting this low seismic activity based on the study. This happens because the design of fixed offshore structures for environmental loading, can provide sufficient resistance against potential low seismic effects.